Criminalistic Turns of the Murder Case in Pécs on Palahegyi Street in 1974 (Academic Journal of Internal Affairs, 2020)
In 1974 an unknown perpetrator killed a 69-year old woman in her very modest house, which was in Pécs on Palahegyi street. The brutal attacker had beaten 22 times the victim’s head with a suddenly picked up charcoal iron. As after one year of widespread investigation the offender was not found, the investigation was discontinued. But in 1989 the new police criminal chief restarted investigation in this case. Thanks for efficient data gathering was a woman scoped, whose personal description, age and personal circumstances were very similar to them of the suspect. The study illuminates strong and weak points, criminalistic lessons of the first and the second investigation.
Keywords: criminalistics; material remains; identification; murder